Glutamate and GABA immunocytochemical electron microscopy in the hippocampal dentate gyrus of normal and genetic absence epilepsy rats - ONAT, FİLİZ; ŞİRVANCI, SERAP (ELSEVIER SCIENCE BV, 2005)
It is generally accepted that absence epilepsy results from the impairment of GABAergic and glutamatergic neurotransmission. In particular, besides excessive GABA mediation within the thalamo-cortico-thalamic circuit in absence epilepsy, neuronal networks of the hippocampus have recently received attention. In the present study, we examined the density of glutamate and GABA neurotransmitter immunolabeling in the dentate gyrus of the hippocampus of genetic absence epilepsy rats from Strasbourg (GAERS) compared to the control group. GABA and glutamate were found to exist in synaptic vesicles of the mossy fiber terminals of the control and GAERS groups. The density of glutamate immunolabeling within the mossy fiber terminals in the hilar region of GAERS hippocampus was found to be significantly decreased compared to the control group. There was no difference in the density of immunolabeling within GABA nerve terminals between GAERS and control group. The findings of this study suggest that mechanisms underlying absence seizures in GAERS may also manifest themselves in other brain regions such as the hippocampus. The presence of GABA within synaptic vesicles of mossy fiber terminals, as revealed by high resolution ultrastructural immunocytochemistry, has provided additional evidence to the possible modulatory role of GABA on synaptic transmission between the mossy fiber and the target cell. Published by Elsevier B.V.
Keywords: GAERS; hippocampus; ultrastructure; glutamate; GABA; EXCITATORY GRANULE CELLS; MOLECULAR LAYER; FASCIA-DENTATA; MOSSY FIBERS; AMINO-ACIDS; IMMUNOREACTIVITY; EXPRESSION; LOCALIZATION; TRANSPORTERS; RECEPTORS